Optimization of the extraction process of antioxidant compositions from Glycyrrhiza uralensis using the response surface method (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
This study aimed to optimise and evaluate the antioxidant activity of Glycyrrhiza uralensis root extract using a simple heating method. The optimisation of extraction conditions was conducted using the Response Surface Methodology (RSM) and a Box-Behnken design (BBD), focusing on variables such as temperature, ethanol concentration, extraction time, and solvent-to-material ratio. The total phenolic content (TPC) and total flavonoid content (TFC) were used as response variables. The optimal extraction conditions were determined to be a temperature of 58°C, ethanol concentration of 56%, a liquid-to-solid ratio of 30 mL/g, and an extraction time of 190 minutes, resulting in TPC and TFC values of 158.81 mg GAE/g and 122.15 mg QE/g, respectively. The extract exhibited considerable DPPH and hydroxyl radical scavenging effects. These findings suggest that the optimized extraction method not only simplifies the process but also enhances the scalability and cost-effectiveness of industrial applications.